Information professional during a process of sales of information services through Whatsapp business - Oliveira, Dalbert Marques (2019)
This paper describes how the Information Professional manages information during a sales process of information services through WhatsApp Business. Such an approach is justified due to the great importance that information currently assumes, as well as the increasingly common practice of information exchange through online, peer or group dialogues. Realizing this reality, dozens of companies have specialized in creating and marketing - often imperceptible to the user – of channels and tools that enable this information exchange. These channels and tools represent new challenges and opportunities for the Information Professional and for the whole society. Among the challenges, it's possible to mention issues related to the collection, processing, storage, management, analysis, maintenance, sharing and privacy of information. With respect to opportunities, we note the use of information as a bargaining chip or even as a product. Among these tools that enable the exchange of information between peers or groups is the WhatsApp application and its Business version. The aim of this paper is to address various aspects of this use, taking advantage of a real case of selling information about Portugal to individuals interested in the country. In this paper it was possible to verify that WhatsApp Business has numerous tools that make it possible to sell informational services online, however the Information Professional should be competent to solve a number of problems and be able to take full advantage of this tool, the WhatsApp Business.